Deposition of a-C:H films on a nanotrench pattern by bipolar PBII&D. (17th May 2016) - Hirata, Yuki; Nakahara, Yuya; Nagato, Keisuke; Choi, Junho
Abstract: In this study, hydrogenated amorphous carbon (a-C:H) films were deposited on a nanotrench pattern (300 nm pitch, aspect ratio: 2.0) by bipolar-type plasma based ion implantation and deposition technique (bipolar PBII&D), and the effects of bipolar pulse on the film properties were investigated. Moreover, the behaviour of ions and radicals surrounding the nanotrench was analyzed to clarify the coating mechanism and properties of the a-C:H films on the nanotrench. Further, thermal nanoimprint lithography was carried out using the nanotrench pattern coated with a-C:H films as the mold, and the mold release properties were evaluated. All nanotrench surfaces were successfully coated with the a-C:H films, but the film thickness on the top, sidewall, and bottom surfaces of the trench were not uniform. The surface roughness of the a-C:H films was found to decrease at a higher positive voltage; this happens due to the higher electron temperature around the nanotrench because of the surface migration of plasma particles arrived on the trench. The effects of the negative voltage on the behaviour of ions and radicals near the sidewall of the nanotrench are quite similar to those near the microtrench reported previously (Park et al 2014 J. Phys. D: Appl. Phys . 47 335306). However, the positive pulse voltage was also found to affect the behaviour of ions and radicals near the sidewall surface. The incident angles of ions on the sidewall surface increased with the positive pulse voltage because the energy of incoming ions on the trench decreases with increasing positive voltage. Moreover, the incident ion flux on the sidewall is affected by the positive voltage history. Further, the radical flux decreases with increasing positive voltage. It can be concluded that a higher positive voltage at a lower negative voltage condition is good to obtain better film properties and higher film thickness on the sidewall surface. Pattern transfer properties for the nanoimprint formed by using nanotrench molds were greatly improved by the a-C:H films owing to the resultant reduction in the mold release force.